The triple role of family mothers in the "Cuna más" program of the district of Huancán – Huancayo - Fabián Arias , Eugenia (2020)
This article addresses the triple role of the Mothers of the Family of the "Cuna más" Program of the District of Huancán - Huancayo; The research is directed by a mixed basic type approach, descriptive level and the instrument was the questionnaire. The findings were; high percentage of mothers who dedicate themselves to the reproductive role based on food preparation, household cleaning and childcare, receiving minimal support from their partners or a female relative in the case of single mothers, followed by the productive role inserted in Informal activities with flexible working hours and laughable income below the vital minimum, and a limited percentage of active participants in organized instances. In conclusion, mothers fulfill a triple role, most fulfill the reproductive role followed by the productive role and their participation in the community role is minimal.